The proceedings of the 13th Australasian Conference on Mathematics and Computers in Sport (ANZIAM MathSport, 2016)
A major goal of the Mathsport conference is to provide a stage for leading thinkers in sports analysis in the Asia-Pacific to share some of their recent work and how it is making an impact in sport. This proceedings includes information about the 39 talks to be given at Mathsport 2016: three keynote talks, two guest talks, six talks on the AFL, five talks on analytic methodologies of general application, five on cricket, four on gambling, three on rugby, two on golf, two on tennis and one each on seven other areas.13. Australasische